Analysis Level of Understanding Software Engineering Student in Cisarua Vocational High School on Algorithm Materials: A Mini Research - Sasmita, Firdamdam; Mulyadi, Yadi; Sumarto, Sumarto (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
The first objective of this study was to determine the distance level of understanding of students and teachers in software majors at SMKN 1 Cisarua. And for the second purpose, the author wants to know the cause of students who excel or do not understand the yahoo material. The research method used is descriptive-based qualitative. The respondents consisted of 3 people, namely teachers, students who excel, and students who do not achieve. Structured interviews, new interviews, recorders, and test sheets were used as tools for collecting data. Each question posed to the respondent is compiled based on the performance criteria in the Indonesian National Work Competency Standards. The data analysis technique used is in the form of a proportion formula. The results show that the teacher understands better than students who excel and students who do not. Students who do not excel better understand than students who do not perform well. And one of the factors that cause students to understand the material is a discussion with upper-level students in the RPL department of SMKN 1 Cisarua. And one of the factors that cause students to be unable to understand the material is the discomfort of students using cell phones as a learning medium.